THU0056 A Small Chemical Compound Identified as an ACE2 Activator Prevented Pulmonary Arterial Hypertension Induced by Monocrotaline. (23rd January 2014) - Haga, S.; Tsuchiya, H.; Hara, K.; Doi, A.; Mimori, A.; Ishizaka, Y.
Abstract : Background: Pulmonary arterial hypertension (PAH) is a lethal clinical symptom characterized by progressive increase in pulmonary arterial pressure and causes right ventricular hypertrophy (RVH) with RV failure. Complications of PAH are observed in 10-15% of patients of connective tissue diseases (CTD) that include systemic sclerosis (SSc), systemic lupus erythematosus and mixed connective tissue disease 1, 2 . Recently, we reported that autoantibodies to angiotensin-converting enzyme 2 (ACE2), a homologue of ACE that functions as negative regulator of renin-angiotensin system by converting angiotensin (Ang) II to Ang-(1-7), were detected in a SSc patient who died due to PAH 3 . Moreover, we further detected that CTD-patients were frequently positive for ACE2-autoantibodies that neutralized ACE2 activity. Because recent lines of evidence revealed that deregulation of ACE2 has a positive link with the development of PAH, we here identified a small chemical compound (compound-A) that activates ACE2 activity. Objectives: We identify novel ACE2 activator and evaluate its effect against pathological condition on PAH. Methods: To prepare animal models of PAH, Sprague-Dawley rats were subcutaneously injected with monocrotaline (MCT). Immediately after single injection of MCT, compound-A was continuously administered for 4 weeks by osmotic pumps. Pulmonary compliance was evaluated by echocardiography, and we monitored the ratio of the acceleration time to ejection time (AcT/ET) of pulmonary artery flow for 4 weeks post-infusion (4 wpi). The right ventricular systolic pressure (RVSP) was measured by catheterization at 4 wpi. Expression of brain natriuretic peptide ( BNP ) and transforming growth factor-β ( TGF-β ), which are markers of cardiac failure and lung remodeling, respectively, were also examined at 4 wpi by real-time RT-PCR using RV and lung, respectively. Results: AcT/ET values were significantly reduced in the MCT+vehicle group (n=13). In contrast, co-administration of compound-A significantly improved the AcT/ET value ( P < 0.05, n=9). Co-injection of compound-A also ameliorated the increase of RVSP that was induced by MCT (37.18 ± 4.76 mmHg, vs. 49.76 ± 6.04 mmHg, P < 0.05, n=5 and 3, respectively). Consistent with these clinical signs, compound-A suppressed expression of BNP and TGF-β mRNA that was up-regulated by MCT ( P < 0.05). Conclusions: Compound-A, a novel ACE2 activator, prevented MCT-induced PAH and vascular remodeling. Along together with data that compound-A inhibited the activity of autoantibodies to ACE2 in CTD-patients, we propose that compound-A is a candidate compound that can be useful to PAH in CTD-patients. We also discuss modes of PAH in CTD-patients, and possible application of ACE2 activators as therapeutics for CTD-patients with vasculopathy. References: Galiè N et al . Guidelines for the diagnosis and treatment of pulmonary hypertension. Eur Heart J . 2009; 30: 2493-2537. Yoshida S. Pulmonary arterial hypertension in connective tissue diseases. Allergol Int . 2011; 60: 405-409. Takahashi Y et al . Autoantibodies to angiotensin-converting enzyme 2 in patients with connective tissue diseases. Arthritis Res Ther . 2010; 12:R85-R92. Acknowledgements: This work was supported by Adaptable and Seamless Technology Transfer Program through target-driven R&D, Japan Science and Technology Agency. Disclosure of Interest: S. Haga: None Declared, H. Tsuchiya: None Declared, K. Hara Grant/research support from: Matching research funds of Nippon chemiphar Co. Ltd. and Japan Science and Technology Agency (JST), A. Doi: None Declared, A. Mimori: None Declared, Y. Ishizaka: None Declared